Isolation, Characterization of dihydroflavonol from Coriandrum sativum Seeds - K. Hamed, Nosaiba; A. Gadir, Suad (Gezira Journal of Health Sciences; Vol 14 No 2 (2018), 2018)
تم فصل أول مركب فلافوني من بذور نبات الكزبرة ذو الأهمية الطبية .  المستخلص الكحولي أعطي المركب : 7 ، 5  ثنائي  هيدروكسيل - ׳ 5 ميثوكسيل  ثنائي هيدروالفلافونول ، والذي حددت تركيبته بواسطة  طيف الأشعة  تحت   الحمراء ، طيف الأشعة  فوق البنفسجية ، طيف الرنين النووي المغنطيسي و طيف الكتلة .                               The authors report on the first isolation of a flavone from the seeds of the medicinally important plant Coriandrum sativum (Apiaceae) . Chromatographic fractionation of the ethanolic extract gave flavonoid (C1) : 5,7,–dihydroxy-5 ׳ - methoxy dihydroflavonol.The structure of this compound was elucidated on the basis of its IR, UV,1H NMR and MS.